2020
DOI: 10.1017/s1742170520000010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of different land uses and soil and water conservation interventions on runoff and sediment yield at different scales in the central highlands of Ethiopia

Abstract: To tackle the problem of soil erosion and moisture stress, the government of Ethiopia introduced a yearly mass campaign where communities get together and implement various soil and water conservation (SWC) and water harvesting (WH) practices. Although the interventions are believed to have reduced soil erosion/sediment yield and enhanced surface and ground water, quantitative information on the impacts of various options at different scales is scarce. The objective of this study was to assess the impacts diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 51 publications
7
29
0
Order By: Relevance
“…In Ethiopia, rainfall-runoff led soil erosion is indeed a fundamental problem (Adgo et al 2013;Tamene and Vlek 2008) and the worst in the world (Hurni et al 2015b). It is considered to be the main driver of land degradation in the rain-feed agricultural areas of the country (Hurni et al 2015b), significantly affecting both on-site and off-site ecosystems (Yaekob et al 2020). The loss of top fertile soil by water erosion creates severe limitations to sustainable agricultural land use, which lead to reduced soil productivity and food insecurity (Hurni et al 2015a;Taddese 2001;Tamene and Vlek 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ethiopia, rainfall-runoff led soil erosion is indeed a fundamental problem (Adgo et al 2013;Tamene and Vlek 2008) and the worst in the world (Hurni et al 2015b). It is considered to be the main driver of land degradation in the rain-feed agricultural areas of the country (Hurni et al 2015b), significantly affecting both on-site and off-site ecosystems (Yaekob et al 2020). The loss of top fertile soil by water erosion creates severe limitations to sustainable agricultural land use, which lead to reduced soil productivity and food insecurity (Hurni et al 2015a;Taddese 2001;Tamene and Vlek 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion not only is jeopardizing agricultural sustainability (Hurni et al 2015a;Tamene and Vlek 2008;Yaekob et al 2020;Yibeltal et al 2019) but also causes streams, lakes, dams, and reservoirs siltation (Haregeweyn et al 2017;Tamene and Vlek 2008;Yaekob et al 2020), and downstream ecosystem impacts (Haregeweyn et al 2016). This can have severe impacts on irrigation agriculture and related investments in different parts of the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic matter loss not only results in reduced water holding capacity and soil degradation but also the loss of plant nutrients which are used to increase yield. This was confirmed by [34] and [6], the major problem to the farm associated with soil erosion come from loss of nutrients and reduced water holding capacity, accounting 50 to 70% of productivity loss. [35] also showed that the effects of erosion from slight to severe on organic matter soil phosphorus level, and plant available water reduces their content from 3% to 1.9%, 31 kg/acre to 20 kg/acre and 7.4% to 3.6%, respectively which in-turn affects productivity of the land.…”
Section: Correlation Of Wheat Yield and Soil Conservation Structuresmentioning
confidence: 73%
“…Similarly, conserved farmland exhibited lower bulk density as compared to un-conserved adjacent farmland at Adaa Berga district, western Ethiopia [ 17 ]. Moreover, soil and water conservation has also a potential to reduce the loss of runoff and soil by improving water retention capacity on treated farm [ 18 ]. The slope gradient treated with soil and water conservation measures for 20 years in Minizr Catchment, Northwest Ethiopia has found a 2.7% slope reduction because of trapped sediment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%